METODE PENENTUAN PADAT PENEBARAN BUDIDAYA PERAIRAN BERDASARKAN KEBUTUHAN OKSIGEN TERLARUT - Santoso, Arif Dwi (Jurnal Hidrosfir Indonesia, 2006)
Environmental parameters of Hurun Bay estuary were monitored at the site of13.5 m3 floating net cages for Epinephelus cromileptes in July 2003. Averagedissolved oxygen inside cages was 3.68 – 6.76 ( average 5.35) mg/L with watertemperature 28.64 – 29.72 (29.09) oC. Salinity 32.69 – 33.0 (32.94) psu andturbidity 0.27 – 13.62 ( 1.15) NTU. Inflow rate of cages was 72 m3/hr withcurrent velocity 2.3 - 5.1 cm/s. Results showed that the functions of respirationrate for correlation between respiration of E. cromileptes and their weight wasy = 0.0065x + 0.1202 meanwhile the functions of optimum stocking density wasY = 1170.7 X -0.5648. On basis of dissolved oxygen budged, estimated optimum stocking density for lower limit was 128 ind/m3 for fish 50 g in average, 60 ind/m3 for fish 200 g and 21 ind/m3 for fish up to 1200 g.